Ball Milling Modified SAPO‐11 Based Catalysts for n‐Decane Hydroisomerization. Issue 22 (11th June 2019) - Ferreira, Luisa; Ribeiro, Filipa; Fernandes, Auguste; Martins, Angela
Abstract: Bifunctional Pt/SAPO‐11 catalysts were prepared using as acid matrix the microporous silico‐aluminophosphate, SAPO‐11, synthesized under microwave radiation. After synthesis, the material was physically modified using a ball mill, changing the grinding time but keeping frequency constant. The metal function (0.5 wt.% Pt) was introduced through mechanical mixture with commercial Pt loaded alumina. The catalysts were characterized by several techniques: powder X‐Ray Diffraction, pyridine adsorption followed by infrared spectroscopy, low temperature N2 adsorption, Hg intrusion porosimetry and electronic microscopy (SEM). The characterization data show modifications of structural and textural properties of the samples as the milling time increases. The catalytic behaviour of Pt/SAPO‐11 materials was studied for hydroisomerization of long chain n ‐alkanes, using n ‐decane as model molecule, aiming to increase the production of mono‐branched isomers. The catalytic results show that, under optimized milling conditions (60 min; 50 Hz) the selectivity into mono‐branched isomers increased when compared with parent catalyst. Abstract : The right time for milling SAPO‐11 materials with interesting surface properties were obtained from the combination of microwave synthesis with 60 min milling post‐modification. Upon Pt introduction, Pt/SAPO‐11 bifunctional catalysts showed enhanced performance in long chain n ‐alkanes hydroisomerization, with improved selectivity into monobranched isomers.